Failed limb salvage by microsurgery, resolved by super-microsurgery - M., Ponce-Hernandez Jonathan; Carmen, Xicohtencatl-Mendoza M. Del; E., Ponce-Xicohtencatl Jonathan; R., Rivera-Sánchez Gilberto; Daniel, Calderon-Hernandez; A., Torre-Anaya Erik; Rodrigo, Banegas-Ruiz (International Journal of Research in Medical Sciences, 2024)
Advances in perforating artery flaps have improved reconstruction in various body parts, particularly the lower extremities, offering benefits in patient quality of life and reduced public health service costs. The use of flaps and microsurgery extends beyond trauma to address conditions like osteomyelitis, tumor resection, osteoarthritis, and post-radiation necrosis. Notably, the superficial circumflex iliac artery perforator flap (SCIP) is highlighted for its thin profile and utility in limb coverage, minimizing donor site morbidity. Microsurgical techniques contribute to limb salvage, reducing amputation risks in severe fractures and post-osteosynthesis complications. A 29-year-old male with cerebral palsy suffered bimalleolar fracture from a high-energy motor vehicle accident. Initial ALT flap reconstruction failed, leading to flap removal and osteosynthesis exposure. After 48 hours, removal of the flap was necessary due to venous thrombosis. Salvage with SCIP flap involved anastomosis to perforators of both posterior tibial artery and vein. This case details a patient with a bimalleolar fracture post-motorcycle accident, initially treated with conventional microsurgery using an ALT flap. Complications arose from venous thrombosis, necessitating flap removal. Salvage was achieved through a SCIP flap with supermicrosurgery techniques, employing 0.5 mm anastomosis for improved functionality and reduced complications in flap recovery and donor site comorbidities. Successful outcomes in microsurgery and supermicrosurgery necessitate comprehensive training. Specialized limb salvage centers must possess specific equipment and instruments for these techniques. The literature reviewed doesn’t indicate contraindications related to the patient’s mental state for the execution of microsurgery and supermicrosurgery.